(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this paper modelling, simulation of MPPT boost converter are described for PV module. MPPT control is implemented using perturb and observe P O method is employed to control boost converter. The power drawn through the PV array is then connected to the DC-DC converter which boosts the voltage by changing the duty cycle. This duty cycle are fed to MOSFET which switches to extract maximum power from the PV system under different operating conditions. The effectiveness of proposed system is shown using MATLAB simulation results. The Matlab simulation of solar PV and Wind with Voltage droop control is successfully done in this paper.